2020
DOI: 10.14309/ajg.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Primary Needle-Knife Fistulotomy Versus Conventional Cannulation Method in a High-Risk Cohort of Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis

Abstract: OBJECTIVES: Successful biliary cannulation is a prerequisite and important component of endoscopic retrograde cholangiopancreatography, but conventional cannulation methods (CCMs) have a postendoscopic retrograde cholangiopancreatography pancreatitis (PEP) rate of 14.1% in patients at high risk for PEP. The aim of this study was to evaluate the effectiveness and safety of needle-knife fistulotomy (NKF), compared with a CCM, when used for primary biliary access in patients at high risk for developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 33 publications
4
44
0
1
Order By: Relevance
“…In our pilot study, NNF was shown to be at least as safe as the traditional access technique with a sphincterotome. A recent study by Jang et al showed that NNF was an effective and safe procedure to gain primary biliary access with a lower PEP rate (25). However, this study only included patients at high risk for PEP and prophylactic NSAIDs were not used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…In our pilot study, NNF was shown to be at least as safe as the traditional access technique with a sphincterotome. A recent study by Jang et al showed that NNF was an effective and safe procedure to gain primary biliary access with a lower PEP rate (25). However, this study only included patients at high risk for PEP and prophylactic NSAIDs were not used in this study.…”
Section: Discussionmentioning
confidence: 97%
“…8 Primary fistulotomy with a needle-knife is also considered safe and prevents PEP. [9][10] In our study, we compared primary precut with very early precut and demonstrated that primary precut in expert hands results in a low risk of PEP, with an overall similar cannulation success rate. 2 There is a widespread belief, even among experts, that precut is a risky technique and is associated with post-ERCP adverse events.…”
Section: Responsementioning
confidence: 90%
“…A rescue infundibulotomy was attempted if the cannulation was difficult. A primary infundibulotomy with a needle knife was attempted, without any attempted cannulation, if the patient had a prominent ampulla of Vater that was expected to be difficult to cannulate [17]. When a guidewire was inadvertently inserted into the pancreatic duct and failed to cannulate the EHD, the double guidewire method was occasionally used.…”
Section: Endoscopic Procedures For Ercpmentioning
confidence: 99%